Assurance and consultancy internal audit roles in information technology risk management. (2nd March 2023) - Elazab, Reda; Gomaa, Ismail
The study explores the extent of internal audit involvement in information technology (IT) risk management. Hence, the paper proposes new assurance and consultancy internal audit roles in IT risk management. Using the data collected from 75 internal auditors through an exploratory study in Egypt, a framework of internal auditing roles in IT risk management is identified. The collected assurance and consultancy internal audit roles in IT risk management might help different parties such as management, audit committee, IT professionals to be more adaptable in assessing and monitoring IT risks. This study's contributions have important implications for exploring the extension of the internal audit profession in IT risk management. The paper is also one of the first to deal with the assurance and consultancy internal audit roles in IT risk management.